Natural extracellular matrix scaffolds recycled from human salivary digests: a morphometric study. (11th February 2016) - Lilliu, MA; Seo, YJ; Isola, M; Charbonneau, AM; Zeitouni, A; El‐Hakim, M; Tran, SD
Abstract : Objective: A challenge in engineering tissues is to supply parenchymal cells with suitable scaffolds which ideally reproduce the extracellular matrix (ECM). This study tested the hypothesis of preserving the 'residual connective tissue' remaining after mechanical and enzymatic release of cells from human submandibular gland biopsies (that we named 'natural ExtraCellular Matrix scaffolds', nECMsc) to be used as recycled natural scaffolds. The objective was to test whether nECMsc and native salivary tissue were comparable morphologically, in ECM proteins composition, and in cell seeding efficiency. Methods: Following cell isolation procedures, nECMsc were kept, either fresh or frozen (sectioned into 12‐ μ m‐thick slices), and examined with high‐resolution electron microscopy (HRSEM) for its three‐dimensional structure, and with picrosirius red staining and immunogold staining for ECM protein composition and distribution, respectively. nECMsc were seeded with human epithelial cells and fibroblasts to assess cell attachment and proliferation in short‐term experiments. Results: Under HRSEM, nECMsc had comparable fiber arrangement to original glands. Histochemical and immunogold‐labeling examinations revealed the presence of collagen types I, III, and IV. Seeded epithelial cells and fibroblasts attached, proliferated (14–55%), and were alive (86–99%) after 4–8 days of culture. Conclusions: nECMsc retained native ECM proteins and maintained their distribution. Seeded cells remained viable on nECMsc.